Size at Birth, Infant Growth, and Blood Pressure at 3 Years of Age - Belfort, Mandy B. (2007)
OBJECTIVES: Our aim was to determine the extent to which infant growth – in weight-for-length – from birth to 6 months is associated with systolic blood pressure (SBP) at 3 years, and to determine whether this association varies with birth size. STUDY DESIGN: In 530 children from the prospective cohort Project Viva, we measured birth length and 6-month weight and length with research standard instruments and SBP at age 3 years with a Dinamap automated recorder. We derived weight-for-length z-scores (WFL-z) and analyzed data with mixed effect regression models. RESULTS: Mean (SD) WFL-z was 0.47(0.75) at birth and 0.70(0.96) at 6 months. Mean (SD) SBP at 3 years was 91.7(9.4) mmHg. After adjusting for confounding variables and birth WFL-z, child SBP was 1.0mmHg (95% CI 0.2, 1.8) higher for each z-score increment in 6-month WFL-z. SBP of children in the lowest birth WFL-z quartile and the highest 6-month WFL-z quartile was 5.5mmHg (95% CI 2.6, 8.4) higher than of children in the highest birth and lowest 6-month WFL-z quartiles. CONCLUSIONS: More rapid increase in weight-for-length, a measure of adiposity, in the first 6 months of life is associated with higher early childhood systolic blood pressure, particularly in children who are thin at birth.